2018
DOI: 10.1103/physrevc.98.014914
|View full text |Cite
|
Sign up to set email alerts
|

Methods for separation of deuterons produced in the medium and in jets in high-energy collisions

Abstract: Coalescence has long been used to describe the production of light (anti)nuclei in heavy-ion collisions. The same underlying mechanism may also exist in jets when a proton and a neutron are close enough in phase space to form a deuteron. We model deuteron production in jets by applying an afterburner, which uses a coalescence mechanism to form deuterons from protons and neutrons produced in PYTHIA for p+p collisions at a center of mass energy √ s = 7 TeV. PYTHIA provides a reasonable description of the proton … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, it has been observed that B 2 at a given transverse momentum decreases as a function of multiplicity, suggesting that the nuclear emission volume increases with multiplicity [2,9,16]. In Pb-Pb collisions the B 2 parameter as a function of p T shows an increasing trend, which is usually attributed to the position-momentum correlations caused by radial flow or hard scatterings [17,18]. Such an increase of B 2 as a function of p T has in fact also been observed in pp collisions at √ s = 7 TeV [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that B 2 at a given transverse momentum decreases as a function of multiplicity, suggesting that the nuclear emission volume increases with multiplicity [2,9,16]. In Pb-Pb collisions the B 2 parameter as a function of p T shows an increasing trend, which is usually attributed to the position-momentum correlations caused by radial flow or hard scatterings [17,18]. Such an increase of B 2 as a function of p T has in fact also been observed in pp collisions at √ s = 7 TeV [6].…”
Section: Introductionmentioning
confidence: 99%
“…From Eqs. (46) and ( 47) one can see √ B 3 should have similar behaviors with that of B 2 as the function of R f . We plot the result of √ B 3 with the dashed line in Fig.…”
Section: Applications In Pp P-pb and Pb-pb Collisions At The Lhcmentioning
confidence: 61%
“…[5,6,42] have also been used to study the light nuclei production. Much effort has been put into the recombination/coalescence factors B A 's in different phenomenological models [6,27,[43][44][45][46][47][48][49][50]. In particular, a consistent understanding for the collision system size and p T dependencies of B A 's measured recently in experiments is urgently necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Eqs. ( 28) and (29) show relationships of light nuclei with primordial nucleons in momentum space in the laboratory frame. They can be directly used to calculate the yields and p T spectra of light nuclei measured extensively as long as the nucleon Lorentz invariant momentum distributions are given.…”
Section: Kernelmentioning
confidence: 99%
“…One is the thermal production [11][12][13][14][15][16], which assumes that (anti-)nuclei are produced from a thermally and chemically equilibrated source like abundantlyproduced mesons and baryons. The other is the coalescence mechanism [1,3,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], in which light (anti-)nuclei are assumed to be produced by the coalescence of the jacent (anti-)nucleons in the phase space. Such production mechanism possesses its unique characteristics.…”
Section: Introductionmentioning
confidence: 99%